Priorização de fatores críticos de sucesso em negócios sociais - Mendes, Rubia Carla (2021)
The vulnerability and lack of opportunities for a significant part of the world's population generates large-scale social inequality. Therefore, it is essential that inclusive and innovative actions are conducive to equality and social development. Social Businesses prioritize social development and balance society. The Critical Success Factors address the elements necessary for the success of an organization. In view of this, the present work aims to propose a tool for prioritizing the Critical Success Factors in Social Businesses, with the purpose of accelerating the social transformation movement and generating significant changes in the culture related to the business world. For this, a systematic literature review was conducted using the Methodi Ordinatio methodology to contextualize the issues addressed by this research. Thirtyfive articles were selected and a Bibliometric Analysis of the studies was performed. After that, a Content Analysis involving the Nvivo [trade mark] software was performed in order to identify the Macro Critical Success Factors, Critical Success Factors of Social Businesses and their variables. After identifying these factors, a validation tool was built to prioritize the Critical Success Factors of Social Businesses, which was applied to 10 Social Businesses operating in the Brazilian market. The data obtained were validated through the AHP (Analytic Hierarchy Process) method and the Likert scale. The results of the research can be considered anchors for several strategic, operational and financial requirements of Social Businesses. The practice of management and measurement, as the protagonists in the field of Social Business become familiar with and use the Critical Success Factors and their variables, brings balance and a solid base for structuring these businesses. With this, strategies are developed throughout the life of these enterprises, which aim to make them consistent and socially responsible, with positive social impacts, structured to maintain their longevity in the competitive market, and mainly, to create opportunities for these businesses to accomplish their purpose before their social mission.